Development of CBT Testlet Model for minimum competency assessment of numeracy literacy at elementary school level - Hamdi, Syukrul; Purnomo, Yoppy Wahyu; Hidayati, Kana; Mu'minin, Nurul (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
The application and development of accurate and reliable technology-based test instruments to assess aspects of knowledge and attitudes is an innovation teachers need to meet the demands of the National Assessment Policy. This research aims to apply the Computer-Based Test (CBT) Testlet Model with Local Wisdom Context as a New Form of Innovation in Supporting the Implementation of Minimum Competency Assessment and Integrated Character Survey. In addition, this research is a new solution for teachers in learning assessment. This research is development research. This research involved 11 experts, each from media and computer experts, material experts from mathematics education study programs, and measurement experts. The test instrument that has been developed has been proven to be valid using content validity and analyzed using the Aiken formula. In contrast, validity has been proven for the character survey using confirmatory factor analysis and reliability estimation using Cronbach alpha. This research produced a testlet model of CBT and test instruments in the form of a minimum competency assessment and an integrated character survey, which have proven valid and reliable.